Blaze the ice dragon - Blade, Adam (Orchard Books, an imprint of Hachette Children's Group London, 2015)
The volcano at Stonewin is frozen over and the lands are blasted with a deadly cold. This is the work of Blaze the Ice Dragon. Can he defeat Blaze and win the next piece of Amulet before it's too late?--Back cover